2a + 3 - 9b - a - 7 Bring like terms together: = 2a - a - 9b + 3 - 7 Combine like terms: = a - 9b - 4
When simplified it is: 2a+8b+4
3A + 9B = 3(A + 3B)
There are 3 terms in the given expression of 6a+9b+15
sample problem 9b + 3a - a + 6+ 2b + 4 terms would be each number or number plus a variable separated by an operation symbol (+ or -) like terms would be 9b and 2b, 3a and -a, and 6 and 4 simply add 9b + 2b (which is 11b) 3a-a (which is 2a) and 6 + 4 (which is 10) your answer would then be 11b + 2a + 10 hope that helped
You would factor 3a + 9b as: 3(a+3b)
The simplified expression is -9a -9b.
3a + 5b - 6a - 9b = -3a - 4b
-28am + 17b
9b + 6 - 8 = -36 9b = -38 b = 4.2222222(repeating)
There are three terms in the given expression.
(27a)2 = 729a2 (9b)3 = 729b3 So (27a)2 + (9b)3 = 729*(a2 + b3)
4a+2b-1a+9b combine all alike variables using commutative property of addition 4a-1a+2b+9b Then add the like variables 3a+11b
That doesn't factor neatly. Applying the quadratic formula, we find two real solutions: (-9 plus or minus the square root of 73) divided by 2. x = -0.2279981273412348 x = -8.772001872658766
It is not an equation but an algebraic expression that can be simplified to: 12b-5a
They are 1, 2, 3, 4, 6, 9, 12, 18, 36,1a, 2a, 3a, 4a, 6a, 9a, 12a, 18a, 36a,1b, 2b, 3b, 4b, 6b, 9b, 12b, 18b, 36b,1a2, 2a2, 3a2, 4a2, 6a2, 9a2, 12a2, 18a2, 36a2,1ab, 2ab, 3ab, 4ab, 6ab, 9ab, 12ab, 18ab, 36ab,1b2, 2b2, 3b2, 4b2, 6b2, 9b2, 12b2, 18b2, 36b2.
(2b - 5)(b + 7)
15b+2-13 = 13b+6-4b 15b-11 = 9b+6 15b-9b = 6+11 6b = 17 b =17/6 or 2 and 5/6
Since 3b is a factor of 9b, it is automatically the GCF.
8b^2 -9b +1 8b^2 -8b -b +1 8b(b-1) - 1(b-1) (8b-1)(b-1)